PENINGKATAN MANAJEMEN USAHA OLAHAN BELIMBING BERBASIS DIGITAL MARKETING PADA UMKM RASADEWA INDONESIA DEPOK - Sunarti, Sunarti; Wulandari, Dewi Ayu Nur; Kuspriyono, Taat; Ardana, Mohamad; Yusuf, Ghufran Faishal; Anwar, Syafina; Syam, Amandasyifa (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. The initial idea for the UMKM business, Rasadewa Indonesia Depok, saw the potential for starfruit to be used as a souvenir typical of the city of Depok. There are no processed food/beverage products made from star fruit and the starfruit icon typical of Depok city, which must be preserved and maintained, and rich in vitamin B. The types of processed products are dodol, juice, syrup, chips, jam, jam pie, chili sauce and tengteng, various variants, sizes and flavors. The problem with partners is that the reach of the marketing network is not wide, partners market their products conventionally by opening displays at home, consigning to shops, participating in exhibitions/bazaars, lack of knowledge to develop their business and not optimally mastering limited digital marketing/optimization of social media. The aim of the activity is to utilize science and technology to empower the community to improve the management of starfruit processing businesses for the creation of community welfare. The solution is to create a digital marketing website https://rasadewa.id/, and develop business management. The method used is learning by doing, starting with direct observation of the field, monitoring and evaluating the results of the training that has been carried out. The stages of implementation are analyzing the situation and conditions of field surveys, collecting data and classifying problems, discussing with partners, socializing partnerships, preparing for transfer of appropriate technology by creating a digital marketing website, providing guidelines for using the website, training, simulation and website assistance, business management, as well as monitoring, evaluating and continuing community service activities. Abstrak. Ide awal usaha UMKM Rasadewa Indonesia Depok melihat potensi buah belimbing dijadikan oleh-oleh khas kota Depok, belum ada olahan produk makanan/minuman berbahan buah belimbing dan belimbing icon khas kota Depok harus dilestarikan dan dipertahankan, serta kaya akan vitamin B. Jenis olahannya dodol, jus, sirup, keripik, selai, pie selai, sambel dan tengteng, berbagai variansi, ukuran dan rasa. Permasalahan mitra jangkauan jaringan pemasaran belum luas, mitra memasarkan produknya secara konvensional dengan membuka display di rumah, konsinyasi ke toko-toko, mengikuti pameran/bazar, minim pengetahuan untuk mengembangkan usahanya dan belum maksimal menguasai limited digital marketing/optimasi media sosial. Tujuan kegiatan memanfaatkan IPTEK pemberdayaan masyarakat peningkatan manajemen usaha olahan buah belimbing demi terciptanya kesejahteraan masyarakat.Solusinya membuat website digital marketing https://rasadewa.id/,dan pengembangan manajemen usaha. Metode yang digunakan learning by doing, diawali peninjauan langsung kelapangan, monitoring dan evaluasi dari hasil pelatihan yang sudah terlaksana. Tahapan pelaksanaannya adalah analisa situasi dan kondisi survei kelapangan, pengumpulan data dan klasifikasi permasalahan, berdiskusi dengan mitra, sosialisasi kemitran, persiapan transfer teknologi tepat guna dengan membuat website digital marketing, menyediakan panduan penggunaan website, pelatihan, simulasi dan pendampingan websitenya, manajemen usaha, serta adanya monitoring, evaluasi dan keberlanjutan kegiatan pengabdian.